Manajemen Memakmurkan Masjid Baiturrahman Melalui Gerakan Kegiatan Remaja Masjid Komplek BPK IV Kecamatan Kebon Jeruk - Hageng Setyo Bintoro; Totong Heri (Departement of Mathematics Education, 2024)
This research is motivated by the lack of enthusiasm among congregants to enrich the mosque. The insufficient motivation of congregants in enriching the mosque has become a problem in the local community, where there is a magnificent mosque building but a lack of religious activities. Isn't it that when religious activities are filled in the mosque, congregants gain broader knowledge about religion? Therefore, young people become the regeneration of local community leaders, and if there are no weekly gatherings in the mosque, it becomes difficult for young people to expand their religious knowledge. Because having religious activity agendas in the mosque is one form of our devotion to Allah SWT. The problem in this research is how to manage to enrich Baiturrahman Mosque through the Youth Movement Activities in the BPK IV Complex of Kebon Jeruk Sub-district. The purpose of this research is to determine how to manage to enrich Baiturrahman Mosque through the Youth Movement Activities in the BPK IV Complex of Kebon Jeruk Sub-district. Informants in this study consisted of the RT Chairman, Mosque DKM Chairman, Religious Affairs Department, Advisory Department, and Youth Department. The research data was collected through interviews, observations, and documentation, and analyzed using a qualitative descriptive method, which describes and presents phenomena with words or sentences, and then the data obtained is used to draw conclusions. The results of the data analysis conclude that the Management of Enriching Baiturrahman Mosque through the Youth Movement Activities in the BPK IV Complex of Kebon Jeruk Sub-district applies mosque management through local youth activities in enriching the mosque.